The Role of Human Relations in Increasing Employee Performance - Tati Hartati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The background of this research was the low performance of the employee, which could be seen from the non optimal task implementation, overdue task completion, and low discipline. In this study, the researcher used analytical descriptive method, also literature study and field study as the instruments. The field study consisted of observation, interview, and questionnaire. The result of the research showed that the human relations done by the Sub-District Head had not been fully implemented based on the principles in human relations. It caused the low employee performance in the Argapura Sub-District Office of Majalengka Regency, so that the hypothesis of the researcher is true and can be accepted.